The Waqifih during the Era of Imam al-Kadhim (peace be upon him): Critical Approaches to the Causes of Emergence - Dr.Ahmed Fadhil Ajimi (Thi Qar Arts Journal, 2025)
Scholarly investigations into the Waqifite movement have conventionally emphasized its correlation with the accumulation of financial resources by certain individuals who were entrusted with the collection of religious dues from the Shi'a community during the period of Imam al-Kazim’s (peace be upon him) imprisonment. This interpretive framework has become entrenched, shaped by sectarian narratives, theological treatises, and historical accounts that chronicle episodes of doctrinal fragmentation and schism within the Shi'a body following the martyrdom of each Imam (peace be upon them).The present study seeks to depart from this conventional and formulaic reading by probing deeper into alternative, latent factors that may have contributed to the emergence and influence of the Waqifite sect. These factors, it is argued, may hold primacy over the materialistic motivations often attributed to certain agents who aligned themselves with the movement out of avarice for the funds under their control—thus relegating the financial dimension to a secondary causal status.If financial gain were indeed the principal impetus behind the formation of this sect, it would have been confined to a limited circle of Imam al-Kazim’s (peace be upon him) representatives. This raises a critical question: why did the Waqifite doctrine persist well into the era of the occultation? Such endurance suggests that theological ambiguity and doctrinal misapprehension stand on equal footing with financial incentives in explaining the genesis and proliferation of the sect—especially given that such doctrinal uncertainties predate Imam al-Kazim (peace be upon him) and continued beyond his time.